2019
DOI: 10.1097/md.0000000000016970
|View full text |Cite
|
Sign up to set email alerts
|

HPV testing on vaginal/cervical nurse-assisted self-samples versus clinician-taken specimens and the HPV prevalence, in Adama Town, Ethiopia

Abstract: This study aimed to determine the feasibility of vaginal/cervical nurse-assisted self-sampling (NASS) and the agreement between human papilloma virus (HPV) tests on self-samples versus clinician-taken (CT) specimens.Women participated voluntarily for cervical cancer screening at St. Aklesia Memorial Hospital. Eighty-three women provided a total of 166 coupled self-taken and CT specimens collected. Specimens were stored at room temperature for a maximum of 10 months and analyzed using validated the RIATOL qPCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 30 publications
3
16
3
Order By: Relevance
“…Comparable to previous studies, similar findings have been reported [27,28]. However, several studies have reported a slightly high HPV detection rate in self-collected samples than healthcare worker-collected samples [7,25,29,30]. The differences in the detection rates between both samples may be attributed to the different self-sampling devices and HPV testing methods used.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Comparable to previous studies, similar findings have been reported [27,28]. However, several studies have reported a slightly high HPV detection rate in self-collected samples than healthcare worker-collected samples [7,25,29,30]. The differences in the detection rates between both samples may be attributed to the different self-sampling devices and HPV testing methods used.…”
Section: Discussionsupporting
confidence: 77%
“…However, studies comparing the detection rate of HPV between healthcare worker-collected-and self-collected samples in LMICs are limited. Moreover, the majority of studies have focused on comparing healthcare workercollected and self-collected samples for HPV DNA detection [7,8,[24][25][26] than HPV mRNA detection. This study aimed to compare the positivity of hrHPV DNA and hrHPV mRNA between healthcare workercollected and self-collected samples and investigate the accuracy of the applicator-tampon-based self-collected samples in detecting hrHPV DNA and hrHPV mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies revealed a similar level of agreement as in our study; κ: 0.75 [ 20 ], κ: 0.74 [ 21 ], and κ: 0.71 [ 22 ]. However, other studies in Ethiopia (κ: 0.58) [ 23 ] and Cameroon (κ: 0.52) [ 24 ] reported a lower level of agreement compared to our study. It is uncertain if these differences reflect the different self-sampling devices used, HPV testing methods, population, and/or sample size.…”
Section: Discussioncontrasting
confidence: 99%
“…The included studies used PCR-based but different molecular approaches to characterize the genotype of HPVs. These include Abbott Real-Time HR-HPV PCR [ 31 ], Digene Hybrid Capture 2 HPV DNA test with genotyping Kit HPV GP [ 27 ], PCR based HPV DNA detection [ 26 ], Line probe assay (Inno-LiPA) [ 30 ], Nested PCR [ 32 ], RIATOL qPCR [ 33 ], GP5 + ⁄6+ HPV PCR with Gel electrophoresis [ 29 ], PCR using GP5 + /6 + primers [ 34 ], Reverse line blot hybridization assay [ 25 ] and multiplexed genotyping (MPG) using BSGP5 + /6 + PCR technique [ 28 ] (data not shown in Table 1 ).…”
Section: Resultsmentioning
confidence: 99%